Pendampingan Siswa Sekolah Menengah Sederajat Terhadap Pilihan Kelanjutan Studi Perguruan Tinggi : Assistance for High School Students Regarding Choices for Continuing Higher Education Studies - Maulida, Maulida; Awlawi, Addahri Hafidz; Herwanis, Delfia; Evanirosa, Evanirosa (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The number of senior high school (SMA/MA) graduates in Central Aceh in 2022 reached 48,481; however, the number of students continuing on to higher education remains very low. This study aims to identify factors influencing the low interest of 12th-grade students in pursuing higher education and to provide guidance in study and career planning. The method used was Community-Based Research (CBR), which involved active student participation in the process of identifying problems and finding solutions. The results showed that participants experienced an increased understanding of the importance of higher education, were able to identify barriers such as financial issues and mindsets, and began planning further studies and considering career options after graduating from high school. Furthermore, participants received information about affordable public university alternatives, such as IAIN Takengon, as a relevant solution aligned with the local economic conditions.